(untitled) ("Conference on Universal Science Research 2023", 2023)
Currently, symphysiopathy in pregnant women is considered as one of the variants of the syndrome associated with pregnancy pelvic girdle pain (pregnancy related pelvic girdle pain - PPGP syndrome). This clinical approach is well argued in terms of evidence-based medicine and is generally accepted by the medical community